Accessibility of selenium after in vitro gastrointestinal simulation in biofortified rice genotypes with selenium (Research, Society and Development, 2022)
Biofortification with selenium is an agronomic strategy that aims to increase the levels of this mineral in food. However, in addition to the amount of selenium in the plant, there is a need to also assess how much of the desirable element present in the food would be available to be assimilated by the organism. Considering the high global consumption of rice and the efficiency demonstrated by rice in biofortification studies, the objective of this research was to evaluate grain yield, total phenolic content and selenium accessibility of three rice varieties (Oryza sativa L.) biofortified with selenium. Two ethnovarieties from the Mato-Grossense swamp (Branquinho and Agulhinha Vermelho) and grow crops commercial (Esmeralda) were used, agronomically biofortified with sodium selenate (50 g ha-1). The following parameters were evaluated: Grain yield (g plant-1), total Se concentration (µg 100 g-1 grain), total phenolics (µg EAG 100 g-1 MS), Se concentration after TGI (in vitro) and accessibility (%) of Se. The ethnovarieties Agulhinha Vermelho and Branquinho showed higher productivity, total Se concentration in raw grains and Se concentration after TGI. The grow crops commercial, Esmeralda, presented the highest concentration of total phenolics and the percentage of Se accessibility, however all genotypes presented Se accessibility above 60%.